Fracture analysis on a multiferroic cylindrical shell: Effects of coupled interphase imperfections. (January 2016) - Li, Yong-Dong; Zhou, Kai; Xiong, Tao
When interphases between ferromagnetic and ferroelectric layers become imperfect, the magnetic, electric, and mechanical imperfections may have inter-couplings. A coupled generalized linear spring model is proposed to formulate such inter-couplings. As an application, fracture analysis is performed on a multiferroic cylindrical shell containing an imperfect interphase. Parametric studies are made on the numerical results of the stress intensity factor to reveal the effects of the three kinds of imperfections and their inter-couplings. Three conclusions are drawn: (a) the mechanical imperfection can enhance the stress intensity factors and meanwhile weaken and even prevent the crack interaction across the interphase; (b) the magnetic/electric imperfection cannot affect the cracks independently, and only when it is coupled with the mechanical one can it reduce the stress intensity factor; and (c) the magneto-mechanical and electro-mechanical imperfection couplings are beneficial to reducing the stress intensity factor, but the magneto-electric imperfection coupling cannot affect the cracks.